A review on liquid hydrogen fuel systems in aircraft applications for gas turbine engines - Ebrahimi, Alireza; Rolt, Andrew Martin; Jafari, Soheil; Anton, Jon Huete (Elsevier, 2024)
The transition from traditional aviation fuels to low-emission alternatives such as hydrogen is a crucial step towards a sustainable future for aviation. Conventional jet fuels substantially contribute to greenhouse gas emissions and climate change. Hydrogen fuel, especially "green" hydrogen, offers great potential for achieving full sustainability in aviation. Hybrid/electric/fuel cell technologies may be used for shorter flights, while long-range aircraft are more likely to combust hydrogen in gas turbines. Liquid hydrogen is necessary to minimize storage tank weight, but the required fuel systems are at a low technology readiness level and differ significantly from Jet A-1 systems in architecture, operation, and performance. This paper provides an in-depth review covering the development of liquid hydrogen fuel system design concepts for gas turbines since the 1950s, compares insights from key projects such as NASA studies and ENABLEH2, alongside an analysis of recent publications and patent applications, and identifies the technological advancements required for achieving zero-emission targets through hydrogen-fuelled propulsion.
Keywords: Energy; 34 Chemical sciences; 40 Engineering; Liquid hydrogen; LH2; Hydrogen; Gas turbine; Fuel system; Aircraft engine